SMARCA4-deficient Uterine Sarcoma and Undifferentiated Endometrial Carcinoma Are Distinct Clinicopathologic Entities. (February 2020) - Kolin, David L.; Quick, Charles M.; Dong, Fei; Fletcher, Christopher D.M.; Stewart, Colin J.R.; Soma, Anita; Hornick, Jason L.; Nucci, Marisa R.; Howitt, Brooke E.
Abstract : Undifferentiated and dedifferentiated endometrial carcinomas (UDEC) are aggressive uterine tumors which may show loss of expression of SMARCA4 (BRG1) or SMARCB1 (INI-1). The recently described SMARCA4-deficient undifferentiated uterine sarcoma (SDUS) has a morphology which overlaps with UDEC. In this study, we compared clinical, morphologic, immunohistochemical, and molecular characteristics to identify features which differentiate SDUS from UDEC. Cases of SDUS (n=12) were compared with cases of UDEC (n=84, 55 of which were previously published). Immunohistochemistry was performed for p53, mismatch repair proteins, claudin-4, SMARCA4, and SMARCB1. Targeted molecular profiling was performed on 15 cases. Patients with SDUS were significantly younger than those with UDEC (mean 35.8 vs. 61.2 y, P =0.0001). UDEC and SDUS showed morphologic overlap; however, phyllodiform architecture favored a diagnosis of SDUS (36% vs. 0%, P =0.005), while prominent nuclear pleomorphism was only seen in some cases of UDEC (0% vs. 24%, P =0.15). Compared with SDUS, UDEC more frequently showed TP53 mutations (0% vs. 34%, P =0.03), microsatellite instability (0% vs. 44%, P =0.006), and intact SMARCA4 and SMARCB1 (0% vs. 80%); a panel combining these immunohistochemical markers had a sensitivity of 100% and specificity of 92% in distinguishing SDUS and UDEC. Cases of UDEC had mutations in genes associated with endometrial adenocarcinomas (eg, TP53, PTEN, PIK3CA ) and occasionally SMARCA4, while SDUS was characterized solely by inactivating mutations in SMARCA4 . Disease-specific survival was shorter in SDUS than UDEC (median survival 9 and 36 mo, P =0.01). In conclusion, SDUS occurs in younger patients than UDEC, has a worse prognosis, and in most cases has a distinct molecular and immunohistochemical profile. Abstract : Supplemental Digital Content is available in the text.